Electrochemical sensors based on conducting polymer-polypyrrole - Ramanavicius, A.; Ramanaviciene, A.; Malinauskas, A.
Conducting polymers can be exploited as an excellent tool for the preparation of nanocomposites with nano-scaled biomolecules. Polypyrrole (Ppy)is one of the most extensively used conducting polymers in design of bioanalytical sensors. In this review article significant attention is paid to immobilization of biologically active molecules within Ppy during electrochemical deposition of this polymer. Such unique properties of this polymer as prevention of some undesirable electrochemical interactions and facilitation of electron transfer from some redox enzymes are discussed. Recent advances in application of polypyrrole in immunosensors and DNA sensors are presented. Some new electrochemical target DNA and target protein detection methods based on changes of semiconducting properties of electrochemically generated Ppy doped by affinity agents are introduced. Recent progress and problems in development of molecularly imprinted polypyrrole are considered.
Keywords: CONDUCTING POLYMERS; POLYPYRROLE; BIOSENSOR; DNA SENSOR; IMMUNOSENSOR; MOLECULARLY IMPRINTED POLYMERS; BIOELECTROCHEMISTRY; NANOTECHNOLOGY; NANOBIOTECHNOLOGY